Evolution of percolation properties in nanocomposite films during particle clustering - Starke, T; Johnston, C; Grant, P (2007)
This paper describes the simulation of the effect of nanoparticle clustering on percolation behaviour in a thin polymeric film containing an inhomogeneous distribution of nanoparticles. A monotonic increase in nanoparticle clustering as composite micro-geometry relaxed resulted in the formation of a percolating network followed by a transition to compacted clusters of nanoparticles and a reduction in the percolative flux. Over longer time-scales, coarsening of clusters was dominated by changes in cluster surface morphology and the through thickness flux increased steadily. © 2006 Acta Materialia Inc.